ChemInform Abstract: Recent Developments in the Synthesis and Utilization of Chiral β‐Aminophosphine Derivatives as Catalysts or Ligands. Issue 20 (April 2016) - Li, Wenbo; Zhang, Junliang
Abstract: Review: [78 refs.